A paradeisos at Ramat Rahel and the setting of Zechariah - Mitchell, Christine (Transeuphratène, 2016)
The recently-excavated garden at Ramat Rahel in the Persian province of Yehud is analysed as a paradeisos. The visions of the biblical book of Zechariah are set in the paradeisos at Ramat Rahel, with implications for ideology and date.